Memphis and the paradox of place : globalization in the American South - Rushing, Wanda (New directions in southern studies., 2009)
Celebrated as the home of the blues and the birthplace of rock and roll, Memphis, Tennessee, is where Elvis Presley, B.B. King, Johnny Cash, and other musical legends got their starts. It is also a place of conflict and tragedy - the site of Martin Luther King Jr.'s 1968 assassination - and a city typically marginalised by scholars and underestimated by its own residents. Using this iconic southern city as a case study, this book explores the significance of place in a globalising age.